To rewrite the irrational cube root \( 3^{\sqrt{189}} \) as the product of an integer and another irrational cube root, we can first simplify \( \sqrt{189} \).
-
Simplifying \( \sqrt{189} \): \[ 189 = 9 \times 21 = 3^2 \times 21 \] Now, we can take the square root: \[ \sqrt{189} = \sqrt{3^2 \times 21} = \sqrt{3^2} \times \sqrt{21} = 3\sqrt{21} \]
-
Substituting back into the cube root: Now we can substitute \( \sqrt{189} \) back into our original expression: \[ 3^{\sqrt{189}} = 3^{3\sqrt{21}} \]
-
Rewriting as a power: We can use properties of exponents to rewrite \( 3^{3\sqrt{21}} \): \[ 3^{3\sqrt{21}} = (3^3)^{\sqrt{21}} = 27^{\sqrt{21}} \]
-
Separate integer and irrational cube root: We can express this as: \[ 27^{\sqrt{21}} = 27 \cdot 3^{\sqrt{21} - 3} \]
-
Expressing the second term: Here, we recognize that this does not simplify cleanly; instead, we keep it as the infinite product involving cube roots.
However, since we need to express \( 3^{\sqrt{189}} \) more simply as the cube root term, we can directly express it: \[ 3^{\sqrt{189}} = 3^3 \cdot 3^{\sqrt{21}} = 27 \cdot 3^{\frac{1}{3} \cdot 21} = 27 \cdot \sqrt[3]{3^{21}} \]
So, we can write:
Final expression for \( 3^{\sqrt{189}} \): \[ 3^{\sqrt{189}} = 27 \sqrt[3]{3^{21}} = 27 \cdot 3^{7} \quad \textbf{Final:} \quad 27 \cdot \sqrt[3]{3^{21}} \]
In conclusion, the irrational cube root \( 3^{\sqrt{189}} \) can be expressed as: \[ 27 \cdot \sqrt[3]{3^{21}} \]